Pengaruh Inflasi ,Pertumbuhan Ekonomi dan Kebutuhan Hidup Layak terhadap Upah Minimum Provinsi (UMP) Di Provinsi Kalimantan Selatan - Sayyidah; Muhammad Effendi (PPJP ULM, 2020)
This study aims to (1) determine the influence of the inflation, economic growth,and decent living needs simultaneously to Provincial Minimum Wages in the southBorneo Province; (2) find out the dominant factor in influencing Provincial MinimumWages in South Borneo Province;Purpose including in type purpose descriptive quantitative. While the locationpurpose is the province south Borneo, and the goal is inflation, economic growth,decent living needs, and provincial minimum wages in the South Borneo Province in2004-2018. Data obtained will be analyzed by multiple linear regression using theProgram Eviews version 10.This study shows that the (1) Inflation, Economic Growth, and Decent LivingNeeds at the same time has a significant impact on Provincial Minimum Wages in theSouth Borneo Province in 2004-2018. (2) This study also indicates that Decent LivingNeeds is the dominant factor affecting Provincial Minimum in South Borneo Provincein 2004-2018.